Corrigendum: Pešić M, Radović S, Rakić T, Dželetović Ž, Stanković S, Lozo J. Insights into the response of miscanthus x giganteus to rhizobacteria: Enhancement of metal tolerance and root development under heavy metal stress. Arch Biol Sci. 2024;76(2):205-21. https://doi.org/10.2298/ABS240301014P - Editorial (Archives of Biological Sciences)
The authors of the article: Pešić M, Radović S, Rakić T, Dželetović Ž, Stanković S, Lozo J. Insights into the response of Miscanthus x giganteus to rhizobacteria: enhancement of metal tolerance and root development under heavy metal stress. Arch Biol Sci. 2024;76(2):205-21 have informed the Editorial Office of the following error in the affiliation of the first author Pešić Mila. Next to the name “Institute of Soil Science” is “University of Belgrade”, which is incorrect because this Institute is not a member of the University of Belgrade. The authors have requested for this error to be corrected. Therefore, the journal is publishing this Corrigendum. Mila Pešić’s affiliation should be as follows: 1University of Belgrade – Faculty of Biology, Belgrade, Serbia, and 2Institute of Soil Science, Belgrade, Serbia. Link to the corrected article 10.2298/ABS240301014P